Higher Accuracy of Arthroscopy Compared to MRI in the Diagnosis of Chondral Lesions in Acute Ankle Fractures: A Prospective Study - Ali Darwich; Dominik Nörenberg; Julia Adam; Svetlana Hetjens; Mohamad Bdeir; Andreas Schilder; Steffen Thier; Sascha Gravius; Ahmed Jawhar (Diagnostics, 2024)
Even after successful surgery for acute ankle fractures, many patients continue having complaints. A possible explanation is the presence of concomitant chondral lesions. The aim of this study is to investigate the accuracy of MRI compared to that of arthroscopy in the assessment of chondral lesions in acute ankle fractures. In this prospective single-center study, patients presenting with acute ankle fractures over a period of three years were identified. A preoperative MRI was performed within a maximum of 10 days after trauma. During surgery, ankle arthroscopy was also performed. The International Cartilage Repair Society (ICRS) cartilage lesion classification was used to grade the detected chondral lesions. To localize the chondral lesions, the talar dome was divided into eight zones and the tibial/fibular articular surfaces into three zones. In total, 65 patients (28 females) with a mean age of 41.1 ± 15 years were included. In the MRI scans, 70 chondral lesions were detected (69.2% of patients) affecting mostly the tibial plafond (30%) and mostly graded as ICRS 3. The mean lesion area measured was 20.8 mm2. In the arthroscopy, 85 chondral lesions were detected (70.8% of patients) affecting mostly the medial surface of the talar dome (25.9%) and mostly graded ICRS 3. The mean lesion area measured was 43.4 mm2. The highest agreement between the two methods was observed in the size estimation of the chondral lesions. The present study shows the reduced accuracy of MRI when compared to arthroscopy in the assessment of traumatic chondral lesions in the setting of acute ankle fractures especially regarding lesion size. MRI remains an essential instrument in the evaluation of such lesions; however, surgeons should take this discrepancy into consideration, particularly the underestimation of chondral lesions’ size in the preoperative planning of surgical treatment and operative technique.